Recent Advances in Microemulsion Properties Prediction for Enhanced Oil Recovery - Yee et al., Hon Vai (International Journal of Advanced Science and Technology, 2020)
Optimum chemical enhanced oil recovery (CEOR) formulation design using surfactant requires the formation of microemulsion at ultralow interfacial tension (IFT). Numerous laboratory tests are required to attain the optimum formulation. Advancement in computational technology enabled the use of molecular scale simulations to provide information that cannot be extracted from experimental data alone and gain insights on microscopic phenomena of microemulsion. In this paper, we provide an extensive review on the ability of various multiscale molecular simulation approaches: Molecular Dynamics (MD), Monte Carlo (MC) and Dissipative Particle Dynamics (DPD), to predict thermophysical and structural properties of microemulsion. In addition, we also reviewed empirical models to statistically link structure and properties of surfactant molecules through Quantitative Structure-Property Relationship (QSPR) approach. A systematic use of molecular modeling tools developed and optimized over the last decades to improve the efficiency in optimum CEOR formulation design is presented and discussed. It is demonstrated that molecular simulation is a powerfool tool to analyze both macroscopic properties and microscopic phenomena of microemulsion under any thermodynamic conditions, especially at extreme conditions where experiment is unable to attain.